Summary of recommendations on the study of trade obstacles of the Association of Caribbean States (ACS Port of SpainTT, 1998)
Makes recommendations on trade policy; trade liberalization committments in integrational schemes; tariff measures; non-tariff measures; and, trade investments and financing systems.
Keywords: TRADE POLICY